PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA NON FISIK DAN KETERAMPILAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN LAPANGAN - Wenny Pebrianti (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2023)
The purpose of this research is to know the effect of Job Satisfaction, Non Physical Work Environment, and Work Skills on Work Productivity of Field Employees at PT. Source of Prime Results in Serawai District. This research uses quantitative analysis with descriptive form. This research was conducted at PT. Excellent Source of Results in Batu Ketebung Village, Serawai District, Sintang Regency. The population in this study were field employees in the harvest division in one of the divisions in this company which had employees in the harvest division and the sample in this study was 53 respondents using saturated sampling technique (census). The data analysis model used in this study uses SPSS for windows 21. Based on the results of hypothesis testing, it shows that the variables of job satisfaction, non physical work environment, and work skills have a significant effect on the work productivity of field employees at PT. Source of Prime Results.